Are we a respectful people - Harner, Ivey Frances (My University, 1893)
Introduction: As each new nation steps out upon the field of the political and social world, it must face the criticism and censure of those who have established their places in the rank of nations. Our country has not been an exception and looking at us from the standpoint of foreign nations and people, we doubters deserve many of the severe attacks made on our manners and customs or more properly – lack of manners and customs. It is to a question growing out of this, that I wish to call your attention – Are We a Respectful People?
Citation: Harner, Ivey Frances. Are we a respectful people. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Political; Social world; People; Respect; Theses; Manuscripts (documents)